Respon Pertumbuhan dan Protein Microgreens Bayam dan Kangkung pada Media yang Berbeda - Suminar, Ratna; Adrialin, Gian Sapta (J-Plantasimbiosa, 2025)
The decreasing area of agricultural land due to conversion to residential use threatens food security and the sustainability of the agricultural sector, so efficient and nutritious cultivation alternatives are needed. Microgreens, young vegetables that are rich in nutrients and can be cultivated on limited land, are a potential solution whose success is greatly influenced by the growing medium. This study aimed to analyze the effect of growing media on the growth and protein of spinach and kale microgreens. The research was conducted in Jambewangi in August-November 2024 using a two-factor completely randomized design (CRD), namely planting media (husk charcoal, cocopeat, Malang sand, and rockwool) and vegetable types (kale and spinach greens), each with three replications. The results showed a significant interaction between vegetable species and planting media on the fresh weight of plants at the age of 14 HST. The best treatment was found in husk charcoal × kale, cocopeat × kale, and rockwool × kale. The highest protein content was recorded in sand × spinach (6.05%), while the highest total chlorophyll was in cocopeat × kale (38.80 µmolm-²). The selection of appropriate growing media proved to have a significant effect on the vegetative growth and nutritional quality of microgreens.